ANALISIS FAKTOR KEBERHASILAN UMKM AYAM GEPREK DALAM MENARIK KONSUMEN DI ERA DIGITAL - Miftah Komala Putri; Elis Qurota A'yun; Ulfa Yulia Rahmi; Muhamad Rifki; Aliyah; Diniya Ningtias Dini (STKIP Subang, 2025)
This study is intended to investigate and analyze the extent to which the success of MSMEs of geprek chicken has an impact on attracting consumers. Digital transformation has made MSMEs one of the main pillars of the national economy, including by encouraging the formation of new job opportunities, improving living standards, and growing innovations based on local wisdom. MSMEs in the culinary field have great opportunities to develop, considering that food and beverage consumption is a primary need that never recedes in society. Geprek chicken is one of the most popular culinary delights, also followed by many other business actors, thus creating tight competition between geprek chicken sellers. This study used a qualitative approach with a data collection method in the form of interviews, involving business owners and consumers as the main informants. The results of the data collection were analyzed to determine the marketing strategies implemented, competitive advantages, and various aspects that determine buyer decisions. The conclusion of the study shows that the factors that contribute to the success of Ayam Geprek Sedulur include superior product quality with original caplak chili sauce, a strategic location near campus, students, and workers in the city of Serang, affordable prices, and friendly and fast service. In addition, the diversity of menus offered and digital promotions through food delivery platforms also play an important role in attracting customers.